Engineering Multifunctional Hydrogel With Osteogenic Capacity for Critical-Size Segmental Bone Defect Repair - Zheng, Shaowei; Zhong, Haobo; Cheng, Hao; Li, Xu; Zeng, Guowei; Chen, Tianyu; Zou, Yucong; Liu, Weile; Sun, Chunhan (Frontiers in Bioengineering and Biotechnology, 2022)
Treating critical-size segmental bone defects is an arduous challenge in clinical work. Preparation of bone graft substitutes with notable osteoinductive property is a feasible strategy for critical-size bone defects. Herein, a biocompatible hydrogel was designed by dynamic supramolecular assembly of polyvinyl alcohol (PVA), sodium tetraborate (Na2B4O7), and tetraethyl orthosilicate (TEOS). The characteristics of supramolecular hydrogel was evaluated by rheological analysis, swelling ratio, degradation experiments, and scanning electron microscope (SEM). In vitro experiments, this TEOS-hydrogel had self-healing property, good biocompatibility, and induced osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs) by up-regulating the expression of Runx-2, Col-1, OCN, and OPN. In segmental bone defects rabbit models, the TEOS contained hydrogel accelerated bone regeneration, thus restoring the continuity of bone and the recanalization of medullary cavity. The above results demonstrated that this TEOS-hydrogel has the potential to realize bone healing in critical-size segmental bone defects.